Blood Lead Levels in Pregnant Women and the Source of Exposure in Northern Coastal Area of Brebes Regency - Nova Amalia Sakina; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2018)
Background: Lead has no advantage for health, pregnant women are vulnerable to lead exposure. Blood Lead Levels (BLLs) in pregnant women that exceed the quality standard in accordance with Center for Disease Control (CDC) (>5 μg/dL) can encounter spontaneous miscarriage and fatigue easily during pregnancy, BLLs in pregnant women < 10 μg/dL can induce health problem during pregnancy such as hypertension, preeclampsia, and eclampsia which is the cause of mortality in pregnant women and high maternal mortality. The aim of study to measure BBLs and the source of exposure.Methods: Pregnant women in 2nd and 3rd trimester were recruited in 4 Subdistricts. Cross sectional study is used with 86 pregnant women located in Wanasari Subdistrict, Bulakamba Subdistrict, Losari Subdistrict and Tanjung Subdistrict with purposive sampling method. BLLs during pregnancy were determined by Atomic Adsorpiton Spectrometer.Results: The results shows that mean of BLLs in pregnant women in this study were 42.437 + 19.758 μg/dL. The source of lead exposure are the habit of consuming seafood (44.2%), wrapping food using newspaper (80.2%), being involve in agricultural activity (37.2%), and passive smoking (70.9%).Conclusions: To recapitulate, BBLs in pregnant women in the northern area of Brebes Regency have exceeded the standard set by the CDC of 5 μg/dL. The dominant source of lead exposure are the habit of wrapping food using newspaper and passive smoking.